A diplomacia de ascensão pacífica como estratégia de política externa da China: as relações com o Vietnã e as disputas sobre as ilhas - Amaral, Gabriela Cristina Granço do [UNESP] (2013)
The rapid rise of China and its growing power have broadened the questions about what he will do to achieve the prominence that judges deserve: whether to continue accepting international order that is called and in which developed its accelerated growth path, or if you prefer vai contest this order, or some of its basic components. The dissertation examines China's relations with Vietnam, especially the dispute over the islands of the South Sea, to the Chinese, or East Sea, to the Vietnamese. The goal is to see how it applies in this case diplomacy of peaceful rise, expression adopted in 2003, and wants to signal that China's interest in ascend without causing damage to other country without undermining international order, ie the compormisso China to promote the development of their country and the other through cooperation and peace. Both countries have ancient territorial disputes around islands located in a region of great interest to the security and the external projection of China. The dissertation examines the foreign policy of nationalism in the weight issue and examines the ramifications of diplomatic dispouta on the islands.